(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Teaching a foreign language, specifically English, in the Finnish primary education system is a topic of interest due to the growing importance of language proficiency in a globalized world. These abstract aims to provide an overview of the current practices, challenges, and potential improvements in teaching English as a foreign language in Finnish primary schools. The Finnish education system is known for its high-quality standards and innovative approaches to teaching. English is typically introduced as a foreign language in Finnish primary schools, with students starting to learn it at a young age. The curriculum emphasizes communication skills, vocabulary building, grammar, and cultural understanding.